Renovace RD na budovu s téměř nulovou spotřebou energie - Bárta, Martin (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Cílem mé závěrečné diplomové práce je renovace rodinného domu na dům „s téměř nulovou spotřebou energie“, tedy návrh různých energetických opatření, tohoto stavu dosáhnout.

The diploma thesis contains by renovation of the family House on the “nearly zero-energy consumption building”, the proposal is for a variety of energy measures to achieve this status.
Renovation of the Family House on the Nearly Zero-Energy Consumption Building
Keywords: Nulový dům; fotovoltaické panely; tepelné čerpadlo; pyranometr; intenzita slunečního záření.; Zero house; photovoltaic panels; heat pump; pyranometer; intensity of solar radiation..